Saintific Narrative of Human Creation: Kemenag and Al-Azhar's Interpretation of Surah Al-Hijr Verses 26-33 - Muhammad Faisal; Sumardi Efendi; Siti Nurkhafifah Marisa; Nazar Fadli; Baihaqi Baihaqi (ZAD Al-Mufassirin, 2026)
Several interpretations of the Qur'an in Indonesia have begun to apply this interpretation approach, for example in the interpretation of Al-Zhar to the interpretation of the Ministry of Religion working with LIPI (Institute of Sciences), one of the studies that applies scientific interpretation in the Qur'an is in understanding the creation of humans from the ground in the context of Surah Al-Hijr verses 26-33, the context of the ground in the text of this verse is then interpreted based on the dimensions of knowledge as applied by the interpretation of Al-Azhar and the interpretation of the Ministry of Religion, the purpose of this study is to find out how the interpretation of Al-Azhar and the interpretation of the Ministry of Religion explain the scientific dimensions in the context of the creation of humans mentioned in Surah Al-Hijr verses 26-33. The approach used in this study is descriptive qualitative. The results of this study show that both interpretations, both Al-Azhar and the Ministry of Religious Affairs, both apply scientific interpretation in explaining the creation of humans contained in Surah Al-Hijr verses 26-33. However, the Ministry of Religious Affairs interpretation goes into more depth in revealing aspects of the compounds contained in the soil, which are part of the interpretation of Surah Al-Hijr verses 26-33.